2018
DOI: 10.1111/febs.14610
|View full text |Cite
|
Sign up to set email alerts
|

The catalytic activity of serine hydroxymethyltransferase is essential for de novo nuclear dTMP synthesis in lung cancer cells

Abstract: Structural data are available in the PDB under the accession number 6FL5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 30 publications
(75 reference statements)
3
37
0
Order By: Relevance
“…By contrast AP-MS analysis of SHMT2-Flag identified only the cytosolic BRISC complex in agreement with Zheng and Greenberg [2]. This finding suggests that the SHMT2-Flag protein was localized outside mitochondria similar to the SHMT2α isoform [1,45]. Further structural analysis would be required to better understand the apparent cytosolic localization of SHMT2-Flag.…”
Section: Discussionsupporting
confidence: 75%
“…By contrast AP-MS analysis of SHMT2-Flag identified only the cytosolic BRISC complex in agreement with Zheng and Greenberg [2]. This finding suggests that the SHMT2-Flag protein was localized outside mitochondria similar to the SHMT2α isoform [1,45]. Further structural analysis would be required to better understand the apparent cytosolic localization of SHMT2-Flag.…”
Section: Discussionsupporting
confidence: 75%
“…All proteins resulted mainly tetrameric in solution; the K157S-K158S mutant required the addition of 200 μM pyridoxal phosphate (PLP) to the running buffer to fully populate the tetrameric state, whereas in the absence of PLP it eluted as a mixture of tetramer (55%) and dimer (45%) (Supplementary Figure S4A). The dichroic spectra of the two mutants superpose with the wild-type enzyme and their thermal stability is slightly reduced (Supplementary Figure S4B-C), as observed for other mutations located near the active site or the tetrameric interface (11).…”
Section: Methodsmentioning
confidence: 59%
“…SHMT1 and SHMT2 expression levels are cross-related in lung cancer cells (11,13); however, the mechanisms by which their expression is controlled to ensure the appropriate amounts of each isoform are unknown. We hypothesized that the control may involve the interaction of SHMT1 with the 5′UTR region of the SHMT2 transcripts, since it has been shown that SHMT1 can bind its own RNA at the level of 5′UTR.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations